2021
DOI: 10.24251/hicss.2021.014
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Applications for Higher Educations: A Market Analysis

Abstract: Benefits and applications of virtual reality (VR) in higher education have seen much interest both from research and industry. While several immersive VR applications for higher education have been described, a structured analysis of such applications on the market does not exist. We use design elements from research for applying VR in higher education to analyze available VR apps. The analyzed VR applications were acquired from pertinent online stores to capture the market's state. We analyze the current pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Historically, researchers within the IS field, such as Walsh & Pawlowski [15, p. 297], once pointed out that IVR is "[…] a technology in need of IS research", whereas most seminal IS studies [e.g., [16][17][18] have focused on virtual worlds or environments rather than IVR technology. Moreover, recent IS studies [6] [ [19][20][21] emphasize IVR technology from a broader perspective of education and learning, rather than safety training in particular. In other interrelated fields however, such as human-computer interaction (HCI), engineering, and educational sciences, several studies [10-13] [22-24] stress the importance of advancing the scientific discourse on VR and safety training, especially with an emphasis on producing prescriptive knowledge such as design principles.…”
Section: Research Problem Aim and Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, researchers within the IS field, such as Walsh & Pawlowski [15, p. 297], once pointed out that IVR is "[…] a technology in need of IS research", whereas most seminal IS studies [e.g., [16][17][18] have focused on virtual worlds or environments rather than IVR technology. Moreover, recent IS studies [6] [ [19][20][21] emphasize IVR technology from a broader perspective of education and learning, rather than safety training in particular. In other interrelated fields however, such as human-computer interaction (HCI), engineering, and educational sciences, several studies [10-13] [22-24] stress the importance of advancing the scientific discourse on VR and safety training, especially with an emphasis on producing prescriptive knowledge such as design principles.…”
Section: Research Problem Aim and Questionmentioning
confidence: 99%
“…In the educational sciences, formative features of learning are considered as feasible for evaluating training performance and learning [6]. The formative approach is also desired to incorporate into IVR training/learning environments [19][20], so that instructors and participants can inspect and evaluate critical factors of the training process. Hence, allowing the users to inspect fire hazardousness, its implications for the chain of cause-and-effect around (e.g., fire, smoke, and how to handle it onboard a train), is a feature that the IVR environment needs to implement for instant evaluation (during the training session) and post evaluation (after the training session) [9] [41].…”
Section: Design For Formative Hazard Inspectionmentioning
confidence: 99%
“…The authors conducted three design workshops with different groups of experts and derived a set of design insights that inform the design of agent-based VR learning environments from a human-computer interaction perspective. Furthermore, a recent analysis of VR app stores provides a comprehensive overview of VR learning apps already available on the market [10]. The authors concluded that available apps were mostly designed as short-term learning units that can be used more as a supplement to traditional lectures.…”
Section: Stream 1: Design-oriented Vr Studiesmentioning
confidence: 99%
“…Note that by the time of testing, there were only few apps for learning targeting higher education in the Oculus Quest VR app market [10], and especially for specialized topics such as cybersecurity. Thus, prior to the testing, we conducted preparation works and came up with the idea of watching 360°videos related to cybersecurity on the headset, which were accessible, but did not go into as much technical depth on the cybersecurity topic.…”
Section: Case 3: Cybersecurity On 360°videomentioning
confidence: 99%
See 1 more Smart Citation